Lower body flexibility and body mass index in adolescent recreational practitioners and non-practitioners of Futsal (Research, Society and Development, 2020)
Introduction: Flexibility is a component of physical fitness, important not only for health promotion, but also for performance in several sports. Body mass index (BMI) is an easy and fast method to evaluate the nutritional status of a population. Objective: The objective of the present study was to compare the level of lower body flexibility and BMI between adolescent recreational practitioners and non-practitioners of futsal. Methodology: Twenty futsal players (age 12 ± 1.3 years, weight 48.12 ± 3.71 kg, height 156.53 ± 4.9 cm) and twenty controls (age 11.7 ± 0.9 years, weight 41.73 ± 3.25 kg, height 153.70 ± 4.0 cm) participated in the study. The subjects had their body weight and height assessed using a digital scale and a wall-mounted stadiometer, respectively. The flexibility was assessed through the sit-and-reach test using a modified Wells Bench. One-way ANOVA was used to determine differences between the groups. Result: Futsal recreational athletes presented higher body mass (p < 0.01, d = 1.83), higher BMI (p < 0.01, d = 1.07) and higher flexibility levels (p < 0.01, d = 2.25). Conclusion: The practice of futsal plays an important role in the improvement of body mass management and flexibility. Further studies with other populations are suggested.